Making a difference: Assessing the impact of the EIB's funding to SMEs - Raschid Amamou; Áron Gereben; Marcin Wolski (European Investment Bank (EIB), 2020)
We look at the impact of intermediated funding provided by the European Investment Bank (EIB) on the performance of small and medium-sized enterprises (SMEs) in the 28 member countries of the European Union between 2008 and 2014. We use a combination of propensity score matching and difference-in-differences to evaluate the impact of EIB lending on corporate performance using firm-level data. We find that EIB lending had a positive effect on employment, firm size, investment and innovation capacity, and it also increased firms' leverage. We also find that the positive impact of EIB funding is higher in the countries of Central and East Europe and also in South Europe, while somewhat smaller, yet still significant, in West and North Europe. All in all, our results indicate that EIB-supported funding made a significant and positive difference to the economic and financial performance of the beneficiary SMEs.
Keywords: 330